ANALISIS FAKTOR YANG MEMPENGARUHI ANEMIA PADA IBU HAMIL TRIMESTER III DI KLINIK PRATAMA MAYEN LIMAU MUNGKUR KABUPATEN DELI SERDANG TAHUN 2024 - Vita Ester, Lawolo Mardian (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2024)
Anemia impacts pregnancy, childbirth, the postpartum period, and newborns. It is preval_ent among pregnant women, with 20% affected in the first trimester and 70% in the second and third trimesters. This study aimed to identify the factors influencing anemia in third-trimester pregnant women with hemoglobin levels below 11 g/dL. Using a case-control design and purposive sampling, the study involved 75 participants and 58 respondents (29 cases and 29 controls). Data analysis was conducted using the chi-square test and logistic regression. The results showed that age (OR=5.833, 95% CI: 1.880-18.099, p=0.002), parity (OR=3.148, 95% CI: 1.070-9.264, p=0.035), adherence to taking iron (Fe) tablets (OR=7.283, 95% CI: 2.237-23.715, p=0.001), and frequency of antenatal care (ANC) visits (OR=4.222, 95% CI: 1.409-12.657, p=0.009) significantly influenced anemia in trimester III pregnant women. The study concluded that the most influential factor was adherence to taking Fe tablets, with an odds ratio of 7.283 (95% CI: 2.237-23.715, p=0.001). This indicates that pregnant women who do not consistently take Fe tablets are 7.283 times more likely to experience anemia compared to those who do. The study recommends enhancing health promotion and creating special monitoring programs to ensure pregnant women adhere to taking Fe tablets.